DEA IN CRICKET A New Approach to Target Resetting in ODI and Team Ranking in Test Cricket - Holla, Srineeth (2011)
The following is a dissertation highlighting the use of Quantitative methods in Cricket. The focus, however, is mostly on modelling a framework to assess the performance of teams in an interrupted One-Day Cricket match using Data Envelopment Analysis (DEA). In this form of Cricket, matches are played in limited overs and results are often expected by the end of the day, failing which the match is abandoned. To avoid an abandoned match, match referees usually predict the schedule of rain spells and reduce the number of overs for both teams equally or sometimes in the second batting team. It is often a challenge to judge the performance of teams being allocated different amount of resources. Several attempts were made in the past to determine the outcome but were not ‘fair’. The most salient of them, the Duckworth-Lewis (D/L) method is still used in practice today. Although a method requiring no more than a pocket-calculator, it has challenged the minds of even the experts by its complexity. Many have criticised it for its lack of simplicity and questioned its relevance. The proposed method, viewed as an alternative to the D/L method, is a DEA model with the teams as ‘Decision Making units’ with their different ‘inputs’ being matched to determine the unknown ‘output’ in the form of updated target score. Unlike the D/L method, this method does require the use of formulation and appropriate computer software. An attempt has also been made to compare the performance of test playing nations, to facilitate the reader to get a better understanding of the use of DEA in Ranking. Taking cumulative figures, both batting and bowling strategies of teams are evaluated giving rise to evaluating the overall strategy and rankings. This shall be discussed alongside and compared with the existing forms of Rating such as the Reliance Test Cricket Ratings.